Evaluation Of Humoral And Cell Immunity In Asthma - Hussein, Ali Razzaq; Abed, Wurood Kadhim; Al-Hatimy, Anwer Najih (Medical Science Journal for Advance Research, 2024)
Background: Asthma is a chronic inflammatory airway disease that universally penetrates the globe, across all societies, ages, genders, health statuses, and social statuses. The IgE as a humeral immunity has an essential role in asthma which is caused by the activation of particular IgE receptors expressed by airway structural cells (airway epithelium cells and airway smooth muscle cells) as well as immune-inflammatory cells (mast cells, eosinophils, basophils, and dendritic cells), so that the recent studies have shown a relationship between serum IgE levels, blood parameter, and airway responsiveness. Method: The blood specimens of 42 patients suffering from asthma and 40 healthy controls were collected during the period between June and September (2023). The level of IgE in the specimens was measured by ELISA and blood parameters (Complete Blood Count) were determined by a hematology analyzer (Beckman Coulter C32). Result: In this study, several variables were identified, including age, gender, IgE, and CBC, and found there was no significant (P= 0. 0. 65) differences between the age groups; and the percentage of female patients (n=25, 59.5 %) is insignificant (P=0.64) more than male (n=17, 40.5%). Patients with a family history were significantly (P value= 0.002) higher (64.3%) than cases without a family history of asthma (35.7%). The percentage of smokers was 76.2% and non-smokers was 23.8% but without significant differences. In this study, the level of white blood cells, both total, granulocytes, and non-granulocytes, were significantly (P=0.001) higher in patients than in controls. The average of IgE was significantly higher (296.64±67.85) in asthma patients than in the control group (32.22± 4.59). However, there are no significant (P=0.067) differences in the IgE level between males (263.7±74.2) and females (295.8±73.9). The relationship between IGE and white blood cells was determined, and there were no significant differences between them (except lymphocyte in control, P=0.001) but there is a positive correlation with total WBC, basophile, neutrophil, monocyte, lymphocyte in patients; and basophile and lymphocyte in control. Conclusion: Asthma occurrence is significantly related to family history, humeral immunity (IgE level) and cellular immunity (total WBC and differential WBC); and insignificantly affected by age and gender kind.